Laminate

JP7638068B2Active Publication Date: 2025-03-03TOYO ALUMINIUM KK
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2020050370
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-03-20
Publication Date
2025-03-03
Estimated Expiration
2040-03-20

Smart Images

  • Figure 0007638068000003
    Figure 0007638068000003
  • Figure 0007638068000004
    Figure 0007638068000004
  • Figure 0007638068000005
    Figure 0007638068000005
Patent Text Reader

Abstract

To provide a laminate that can be produced on a large scale and has a layer having water repellency and / or oil repellency hardly peeled or dropped-off.SOLUTION: A laminate 10 forms on a substrate film 11 a porous functional layer 12 including a three-dimensional network structure where fine particles having water repellency and / or oil repellency adhere to each other and a thermoplastic resin. The porous functional layer 12 has a void fraction of 1 vol.% or more and 50 vol.% or less in a region B from a porous functional layer bottom face 12a to the 50% thickness and a void fraction of 50 vol.% or more and 99 vol.% or less in a region A beyond the 50% thickness from the porous functional layer bottom face to a porous functional layer top face 12b, in a thickness direction of the porous functional layer 12.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate having water repellency and oil-water repellency. [Background technology]

[0002] Conventionally, water-repellent or oil-repellent technology has been widely studied for adhesion prevention and mold release applications. In particular, for food, beverages, medicines, cosmetics, and other packaging materials, products have been developed that have been treated with super water-repellent coatings that have a contact angle with water of 150° or more, or super oil-repellent coatings that have a contact angle with oil of 150° or more, with the aim of reducing adhesion of the contents to the packaging materials. In general, super water-repellent and super oil-repellent properties are achieved by modifying the chemical properties through coating, or by modifying the physical properties by imparting fine unevenness.

[0003] For example, Patent Document 1 discloses a method of forming a thin metal film on the surface of a substrate, depositing hydrophobic particles on the surface using a CVD method with an organosilicon compound, and exposing the substrate to an atmosphere containing a similar organosilicon compound to bond the metal film to the hydrophobic particles or to each other with the hydrophobic particles, thereby forming a water-repellent layer with excellent durability.

[0004] Furthermore, Patent Document 2 proposes a technology in which a water-repellent layer containing hydrophobic microparticles and a binder (metal alkoxide) is treated to form a water-repellent layer with excellent durability in which the hydrophobic microparticles do not easily fall off, and the water-repellent layer is further treated into an adhesive layer to enable heat sealing.

[0005] Patent Documents 3 and 4 disclose that a water-repellent surface with excellent durability is formed by imparting fine irregularities to the surface of a substrate by a nanoimprint method (UV curing method, heat curing method). Patent Document 3 uses a UV curing method, and proposes a method in which a mold with a concave structure at a pitch of several hundred nanometers is pressed against a UV curable resin, the resin is cured by irradiating UV light, and convex pillars are formed at a pitch of several hundred nanometers. Patent Document 4 uses a heat curing method, and proposes a method in which a mold with a concave structure at a pitch of several hundred nanometers is pressed against a thermoplastic resin, convex pillars are formed, and then the resin is cooled. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent Publication No. 2014-152389 [Patent Document 2] Patent Publication No. 2017-100778 [Patent Document 3] Patent Publication 2018-187767 [Patent Document 4] Patent Publication No. 2018-95799 Summary of the Invention [Problem to be solved by the invention]

[0007] However, the method of Patent Document 1 requires a step of depositing and growing hydrophobic particles after forming a thin metal film, which poses problems of requiring large-scale equipment and difficulty in mass production.

[0008] In addition, in the technology of Patent Document 2, a super-water-repellent layer is formed by mixing hydrophobic microparticles with tetraethoxysilane (metal alkoxide) as a binder, but the adhesive strength between the super-water-repellent layer and the substrate is weak, and there is a risk that the super-water-repellent layer itself will peel off relatively easily.

[0009] In the methods of Patent Documents 3 and 4, a superhydrophobic layer is formed by nanoimprinting, but the productivity of the nanoimprinting method is lower than that of surface modification by coating, and it is not suitable for industrial-scale production.

[0010] Therefore, a main object of the present invention is to provide a laminate which can be mass-produced and in which a water- and / or oil-repellent layer is unlikely to peel off or fall off. [Means for solving the problem]

[0011] As a result of extensive research into the problems of the prior art, the present inventors have found that the above object can be achieved by employing a specific layer structure, and have thus completed the present invention.

[0012] That is, the present invention relates to the following laminate. 1. A laminate in which a porous functional layer containing a three-dimensional network structure formed by bonding water- and / or oil-repellent particles to each other and a thermoplastic resin is formed on a substrate film, In the thickness direction of the porous functional layer, the porosity is 1 volume % or more and 50 volume % or less in a region from the bottom surface of the porous functional layer to 50% of the thickness, and the porosity is 50 volume % or more and 99 volume % or less in a region from the bottom surface of the porous functional layer to more than 50% of the thickness to the surface of the porous functional layer. A laminate comprising: 2. The laminate according to item 1, wherein the voids in the three-dimensional network structure in at least a region extending from the bottom surface of the porous functional layer to 50% of the thickness thereof are filled with a thermoplastic resin. 3. The laminate according to item 1 or 2, wherein a portion of the porous functional layer is embedded in the substrate film. 4. The laminate according to any one of items 1 to 3, wherein the fine particles have an average primary particle size of 5 to 50 nm. 5. The laminate according to any one of items 1 to 4, wherein a mass ratio of the fine particles to the thermoplastic resin is 50:50 to 80:20. 6. The laminate according to any one of items 1 to 5, wherein the thermoplastic resin includes a polyolefin resin. Effect of the Invention

[0013] According to the present invention, it is possible to provide a laminate which can be mass-produced and in which the water- and / or oil-repellent layer is not easily peeled off or removed.

[0014] In particular, the laminate of the present invention has a porous functional layer containing a thermoplastic resin and a functional particle that forms a three-dimensional network structure, and has a non-uniform structure (preferably a gradient structure) in which the porosity of the porous functional layer is lower near the substrate film and higher near the surface of the porous functional layer. By adopting such a structure, the adhesion between the substrate film and the porous functional layer is increased, and the two have an integral structure, so that the porous functional layer can be effectively suppressed or prevented from peeling off or falling off from the substrate film. Therefore, it is possible to show a certain degree of durability even against a relatively strong frictional force. And such a laminate can be formed, for example, by a predetermined coating liquid as described below. As a result, it is possible to more efficiently provide a laminate that can effectively maintain the desired water repellency and / or oil repellency. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a schematic diagram (conceptual diagram) of an example of a layer structure of a laminate of the present invention. [Diagram 2] FIG. 2 is an image of the layer structure of the laminate produced in Example 1, observed with a scanning electron microscope. [Diagram 3] 1 is a 3D image of a porous functional layer in the laminate of Example 1, created using a FIB-SEM. [Figure 4] FIG. 3 shows an analytical image of the porous functional layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] 1.Laminate The laminate of the present invention (the laminate of the present invention) is a laminate in which a porous functional layer containing a three-dimensional network structure formed by fixing water-repellent and / or oil-repellent fine particles to each other and a thermoplastic resin is formed on a substrate film, In the thickness direction of the porous functional layer, the porosity is 1 volume % or more and 50 volume % or less in a region from the bottom surface of the porous functional layer to 50% of the thickness, and the porosity is 50 volume % or more and 99 volume % or less in a region from the bottom surface of the porous functional layer to more than 50% of the thickness to the surface of the porous functional layer. It is characterized by:

[0017] FIG. 1 is a schematic diagram showing an example of the layer structure of the laminate of the present invention. As shown in FIG. 1, the laminate of the present invention 10 has a porous functional layer 12 formed on a substrate film 11. This porous functional layer 12 is supported by being fixed (adhered) to the substrate film 11. The porous functional layer 12 includes a three-dimensional network structure in which water- and / or oil-repellent fine particles (hereinafter, also referred to as "functional particles" unless otherwise specified) 13 are adhered to each other, and a thermoplastic resin 14. In the laminate of the present invention 10, the thermoplastic resin 14 may be contained either on the periphery or inside of the three-dimensional network structure, but is preferably contained at least in the voids of the three-dimensional network structure as shown in FIG. 1.

[0018] In the thickness t direction of the porous functional layer 12, the porosity is 1% by volume or more and 50% by volume or less in the region between the bottom surface 12a of the porous functional layer and the 50% thickness (t / 2) (hereinafter also referred to as "region B"), and the porosity is 50% by volume or more and 99% by volume or less in the region between the bottom surface 12a of the porous functional layer and the 50% thickness (t / 2) to the surface 12b of the porous functional layer. That is, the density of the functional particles and the thermoplastic resin is high in the region B closer to the base film of the porous functional layer 12, and the density is low in the region A closer to the surface of the porous functional layer. This increases the force of fixing the porous functional layer to the base film, and as a result, the water repellency and oil repellency can be maintained for a longer period of time.

[0019] In the present invention, the thickness t of the porous functional layer is calculated by the following formula, using the horizontal position of the functional particle at the bottom of the three-dimensional mesh structure as the bottom surface 12a of the porous functional layer, the horizontal position of the functional particle at the highest position of the three-dimensional mesh structure as the surface 12b of the porous functional layer, and the position of the bottom surface 11a of the base film 11 as the reference, as shown in Figure 1. Thickness t of the porous functional layer = (distance (height difference) from the bottom surface 11a to the porous functional layer surface 12b) - (distance (height difference) from the bottom surface 11a to the porous functional layer bottom surface 12a)

[0020] 1, in the laminate 10 of the present invention, it is preferable that a part of the porous functional layer 12 (particularly the three-dimensional network structure) is embedded in the base film 11. This can increase the adhesion of the porous functional layer to the base film.

[0021] In the following, each layer constituting the laminate of the present invention, as well as the materials constituting each layer, will be described.

[0022] Base Film The substrate film functions as a support layer that supports the porous functional layer in the laminate of the present invention. Therefore, as long as it has such a function, its material is not particularly limited, and examples thereof include simple substances such as resins (e.g., synthetic resins such as polyester, polyethylene, polypropylene, etc.), fibrous materials (e.g., paper, synthetic paper, nonwoven fabric, woven fabric, wood board, etc.), metals or alloys (e.g., metal foils such as aluminum foil), and glass (glass plate), as well as composite materials and laminated materials thereof.

[0023] In particular, in the present invention, at least one type of resin film selected from the group consisting of polypropylene-based film, polyethylene-based film, and polyester-based film can be suitably used as the base film.

[0024] In particular, when the base film is a resin film, the resin film may be either a stretched film or an unstretched film. Furthermore, the stretched film may be either a uniaxially stretched film or a biaxially stretched film. In addition, various types of resin films that have been subjected to a surface treatment such as a corona treatment may also be used as the base film.

[0025] The thickness of the base film is not limited, and can be appropriately set depending on the material of the base film, the application of the laminate of the present invention, etc. In general, the thickness can be appropriately set within the range of about 20 to 80 μm, but is not limited thereto.

[0026] The surface of the substrate film (particularly the surface on which the porous functional layer is laminated) may be subjected to a surface treatment. This can further increase the adhesion (bonding) between the substrate film and the porous functional layer. Examples of the surface treatment include unevenness treatment using additives (preferably filler particles) and unevenness treatment by embossing. The height of the unevenness is not limited, but is preferably about 5 to 60 μm, more preferably 20 to 50 μm.

[0027] The base film may be either a single layer or a multilayer. For example, a laminate film having a heat seal layer laminated on at least one surface of a resin film can be used as the base film.

[0028] In this case, the heat seal agent for forming the heat seal layer may contain components of known or commercially available sealant films, as well as components used in known or commercially available adhesives such as lacquer-type adhesives, easy-peel adhesives, and hot-melt adhesives.

[0029] The main component constituting the heat seal layer is not particularly limited, and examples thereof include low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, polypropylene, ethylene-vinyl acetate copolymer, ionomer resin, ethylene-acrylic acid copolymer, vinyl chloride-vinyl acetate-acrylic acid ester copolymer, ethylene-ethyl acrylate copolymer, ethylene-methacrylic acid copolymer, ethylene-methyl methacrylate copolymer, ethylene-propylene copolymer, methyl pentaethylene polymer, polybutene polymer, acid-modified polyolefin resins obtained by modifying polyolefin resins such as polyethylene or polypropylene with unsaturated carboxylic acids such as acrylic acid, methacrylic acid, maleic acid, maleic anhydride, fumaric acid, and itaconic acid, polyvinyl acetate resins, poly(meth)acrylic resins, polyacrylonitrile resins, polyvinyl chloride resins, and other heat-adhesive resins, as well as blends of these resins, copolymers containing combinations of monomers constituting these resins, and modified resins.

[0030] In addition, the base film may contain other components within a range that does not impair the effects of the present invention. For example, tackifiers, antiblocking agents, colorants, thickeners, etc. can be mentioned. In particular, in the present invention, antiblocking agents can be preferably used. The antiblocking agent is not particularly limited, and at least one of polyethylene wax, polypropylene wax, silica, inorganic particles, synthetic resin particles, etc. can be preferably added.

[0031] Porous functional layer The porous functional layer in the laminate of the present invention is a layer having water repellency and / or oil repellency and includes a three-dimensional network structure formed by functional particles fixed to each other and a thermoplastic resin.

[0032] The functional particles (particle group) form a three-dimensional network structure by fixing individual functional fine particles in contact with each other. In particular, the three-dimensional network structure is porous (aggregate) and has gaps (pores) formed between the functional particles. The pores may be independent pores or continuous pores, or independent pores and continuous pores may coexist.

[0033] The present invention is characterized in that the porosity of the porous functional layer is relatively higher in region A compared to region B. In other words, the functional particles and thermoplastic resin are more densely packed on the substrate film side of the functional layer. This void distribution (density distribution), in combination with the presence of the thermoplastic resin, increases the adhesion of the porous functional layer to the substrate film, and the high porosity of the functional layer surface (surface unevenness and the presence of an air layer) contributes to long-term maintenance of high water repellency and / or oil repellency.

[0034] The amount of the porous functional layer applied can be appropriately set depending on, for example, the desired water repellency and / or oil repellency, the type of thermoplastic resin used, etc., and is preferably set so as to be within the range of the amount of functional particles applied described below. For example, 0.6 to 5 g / m 2 degree (especially 1~3g / m 2 ), but is not limited to this.

[0035] The degree of water repellency and / or oil repellency of the functional layer is not limited, but it is preferable that the functional layer has the following physical properties: With regard to water repellency, it is preferable that the contact angle with water is 150 degrees or more (so-called super water repellency). With regard to oil repellency, it is preferable that the contact angle with oil is 150 degrees or more (so-called super oil repellency).

[0036] The thickness of the porous functional layer is not particularly limited, but is usually within the range of about 1 to 20 μm, and preferably 1 to 5 μm. By setting the thickness within such a range, even higher water repellency or oil repellency can be obtained.

[0037] The functional particles constituting the porous functional layer are not particularly limited as long as they have water repellency and / or oil repellency. For example, hydrophobic oxide particles can be suitably used.

[0038] As the hydrophobic oxide fine particles, for example, at least one type of particles (powders) of silicon oxide, titanium oxide, aluminum oxide, zinc oxide, etc. Among these, silicon oxide particles are preferable.

[0039] The hydrophobic oxide fine particles preferably have an average primary particle diameter of 5 to 50 nm, and more preferably 7 to 30 nm. The average primary particle diameter can be measured using a transmission electron microscope or a scanning electron microscope. More specifically, the average primary particle diameter can be determined by taking a photograph using a transmission electron microscope or a scanning electron microscope, measuring the diameters of 200 or more particles on the photograph, and calculating the arithmetic average value.

[0040] The nano-level oxide particles can be publicly known or commercially available. For example, silica products include those with the product names "AEROSIL R972", "AEROSIL R972V", "AEROSIL R972CF", "AEROSIL R974", "AEROSIL RX200", and "AEROSIL RY200" (all manufactured by Nippon Aerosil Co., Ltd.), "AEROSIL R202", "AEROSIL R805", "AEROSIL R812", and "AEROSIL R812S" (all manufactured by Evonik Degussa), "Sylo Hobic 100", "Sylo Hobic 200", and "Sylo Hobic 603" (all manufactured by Fuji Silysia Chemical Co., Ltd.). Titania products include those with the product name "AEROXIDE TiO2T805" (manufactured by Evonik Degussa). An example of alumina is fine particles such as "AEROXIDE Alu C" (manufactured by Evonik Degussa) whose particle surfaces have been made hydrophobic by treating them with a silane coupling agent.

[0041] Among these, hydrophobic silica fine particles can be preferably used. In particular, hydrophobic silica fine particles having trimethylsilyl groups on the surface are preferred in that they provide superior non-adhesive properties. Examples of corresponding commercially available products include the aforementioned "AEROSIL R812" and "AEROSIL R812S" (both manufactured by Evonik Degussa).

[0042] As the oil-repellent particles, for example, composite particles in which the oxide fine particles serving as the core have been subjected to a surface treatment to impart oil-repellency can be suitably used.

[0043] The oxide fine particles that become the cores can be at least one type of particles (powders) of silicon oxide, titanium oxide, aluminum oxide, zinc oxide, etc. Among these, silicon oxide particles are preferred.

[0044] Commercially available products may also be used as the oxide particles serving as the core. Examples of silicon oxide include products with the product names "AEROSIL 200" ("AEROSIL" is a registered trademark, the same applies below), "AEROSIL 130", "AEROSIL 300", "AEROSIL 50", "AEROSIL 200FAD", and "AEROSIL 380" (all manufactured by Nippon Aerosil Co., Ltd.). Examples of titanium oxide include products with the product name "AEROXIDE TiO2T805" (manufactured by Evonik Degussa). Examples of aluminum oxide include products with the product name "AEROXIDE Alu C 805" (manufactured by Evonik Degussa).

[0045] The method for preparing the composite particles is not particularly limited, and for example, a polyfluoroalkyl methacrylate resin may be used as a coating material for metal oxide particles (powder), and a coating layer may be formed according to a known coating method, granulation method, etc. More specifically, the composite particles can be suitably prepared by a manufacturing method including a step (coating step) of coating oxide particles with a coating liquid in which a liquid polyfluoroalkyl methacrylate resin is dissolved or dispersed in a solvent.

[0046] In the above-mentioned manufacturing method, the polyfluoroalkyl methacrylate resin can be preferably a liquid at room temperature (25°C) and normal pressure. For example, a copolymer of polyfluorooctyl methacrylate, 2-N,N-diethylaminoethyl methacrylate, 2-hydroxyethyl methacrylate and 2,2'-ethylenedioxydiethyl dimethacrylate can be preferably used as the polyfluoroalkyl methacrylate resin. Commercially available products can also be used as such polyfluoroalkyl methacrylate resin.

[0047] The solvent used in the coating liquid is not particularly limited, and in addition to water, organic solvents such as alcohol and toluene can be used, but in the present invention, it is preferable to use water. That is, it is preferable to use a coating liquid in which the polyfluoroalkyl methacrylate resin is dissolved and / or dispersed in water.

[0048] The content of the polyfluoroalkyl methacrylate resin in the coating liquid is not particularly limited, but is generally about 10 to 80% by weight, preferably 15 to 70% by weight, and more preferably within the range of 20 to 60% by weight.

[0049] The method for coating the surface of the oxide particles with the coating liquid may be any known method, for example, a spray method, a dipping method, a stirring granulation method, etc. In particular, in the present invention, coating by a spray method is particularly preferred because of excellent uniformity, etc.

[0050] After coating with the coating liquid, the solvent is removed by heat treatment to obtain composite particles. The heat treatment temperature is usually about 150 to 250°C, and preferably 180 to 200°C. The heat treatment atmosphere is not limited, but an inert gas (non-oxidizing) atmosphere such as nitrogen gas or argon gas is preferable. In addition, for example, if necessary, a series of steps consisting of the coating step and the heat treatment step can be carried out one or more times. This makes it possible to suitably control the amount of coating, etc.

[0051] The surface of the composite particles thus obtained contains a polyfluoroalkyl methacrylate resin, which has excellent affinity with the oxide particles, and thus can form a strong coating layer with relatively high adhesion on the particle surface, and can also exhibit higher water repellency or oil repellency.

[0052] The amount of the functional particles attached (weight after drying) may be an amount sufficient to form a three-dimensional network structure, but is usually 0.01 to 10 g / m 2 It is preferable that the thickness is 0.2 to 1.5 g / m 2 It is more preferable to set the thickness to 0.2 to 1 g / m. 2 It is most preferable to set the above.

[0053] thermoplastic resin In the laminate of the present invention, the thermoplastic resin contained in the porous functional layer mainly serves to strengthen the adhesion (bonding) between the porous functional layer and the substrate film and between the functional particles in the porous functional layer.

[0054] The type of thermoplastic resin is not particularly limited as long as it has adhesiveness to the base film. For example, various resins such as polyolefin resins, polyamide resins, polyester resins, urethane resins, and acrylic resins can be used.

[0055] In particular, for example, when the substrate film is a polypropylene film, the thermoplastic resin can be preferably a polyolefin resin (particularly a polypropylene-based resin or a modified polypropylene-based resin). Also, for example, when the substrate film is a polyethylene terephthalate (PET) film, the thermoplastic resin can be preferably an acrylic resin, a polyester resin, or the like. In this way, by selecting a thermoplastic resin that has a higher adhesion to the substrate film used, it is possible to further increase the adhesion between the porous functional layer and the substrate film.

[0056] The softening point of the thermoplastic resin used is not particularly limited, but is usually set to about 60 to 150°C.

[0057] The content of the thermoplastic resin is not particularly limited, but it is preferable that the ratio of the functional particles to the thermoplastic resin is about 50% by mass:50% by mass to 80% by mass:20% by mass, assuming that the total of the functional particles and the thermoplastic resin is 100% by mass. This makes it possible to further increase the adhesion between the base film and the porous functional layer, and at the same time, obtain better water repellency or oil repellency.

[0058] 2. Manufacturing method of laminate The laminate of the present invention can be suitably produced, for example, by the following method: That is, a method for producing a laminate having water and / or oil repellency can be suitably adopted, which includes (1) a step of applying a coating liquid containing water- and / or oil-repellent fine particles and a thermoplastic resin to a substrate film (a coating film forming step), and (2) a step of heat-treating the coating film obtained above (a heat treatment step).

[0059] Paint film formation process In the coating film forming step, a coating liquid containing water- and / or oil-repellent particles and a thermoplastic resin is applied to a substrate film.

[0060] The coating liquid usually contains functional particles, a thermoplastic resin, and a solvent. The types of functional particles and thermoplastic resin, and the ratio of the two are as described above. The solvent is not limited and can be appropriately selected depending on the type of thermoplastic resin used. For example, it can be appropriately selected from organic solvents such as alcohol-based solvents (ethanol, methanol, isopropyl alcohol (IPA), hexyl alcohol, etc.), ketone-based solvents (acetone, ketone, methyl ethyl ketone (MEK), etc.), hydrocarbon-based solvents (cyclohexane, normal pentane, normal hexane methylcyclohexane (MCH), etc.), aromatic solvents (toluene, etc.), and glycol-based solvents (propylene glycol, hexylene glycol, butyl diglycol, pentamethylene glycol, etc.).

[0061] The coating liquid may be a solution in which the thermoplastic resin is dissolved in a solvent, but it is preferable that the coating liquid is in the form of a dispersion in which the functional particles and the thermoplastic resin particles are dispersed in the solvent. As a result, when the coating liquid is applied to the base film, the functional particles and the thermoplastic resin particles are uniformly applied, so that the adhesion between the functional particles and the adhesion between the porous functional layer and the base film can be improved while maintaining the properties of the functional particles. When such a dispersion liquid is applied to the base film, many of the functional particles and the thermoplastic resin particles move downward (in the direction of gravity), so that the porosity of the porous functional layer is low in the region B close to the base film of the porous functional layer, and the porosity is high in the region A. In this way, a porous functional layer having a gradient structure can be effectively formed.

[0062] The application method is not particularly limited, and known methods such as roll coating, various gravure coatings, bar coater, doctor blade coating, comma coater, spray coating, brush coating, etc. can be appropriately used.

[0063] After application, a drying step may be carried out as necessary. The drying method is not particularly limited, and may be either natural drying or heat drying. When heat drying is performed, the temperature is usually about 60 to 100°C, and particularly 80 to 90°C. The heating time may be appropriately set depending on the heating temperature, etc., and may usually be about 3 to 30 seconds, but is not limited thereto.

[0064] Heat Treatment Process In the heat treatment step, the coating film obtained in the coating film formation step is heat treated. By the heat treatment, the functional particles and the thermoplastic resin are bonded in the porous functional layer, and the thermoplastic resin is bonded to the base film, so that a laminate having excellent adhesion between the base film and the porous functional layer can be obtained. Furthermore, in the heat treatment step, a part of the functional particles and / or the thermoplastic resin can be embedded in the base film, so that higher adhesion can be obtained, and the base film and the porous functional layer can be more effectively integrated into a structure.

[0065] The heat treatment temperature is preferably set to a temperature range lower than the heat resistance temperature of the base film and equal to or higher than the softening temperature of the thermoplastic resin contained in the porous functional layer. Therefore, for example, if the heat resistance temperature of the base film is 150°C and the softening temperature of the thermoplastic resin is 120°C, the heat treatment temperature can be set to about 120 to 145°C (or, for example, about 125 to 140°C).

[0066] The heat treatment time may be a time sufficient to obtain the desired adhesion, and may be, for example, about 10 seconds to 10 minutes, but is not limited to this.

[0067] 3. Use of laminates The laminate of the present invention can be used in various applications requiring, for example, anti-adhesion performance, antifouling properties, water repellency and / or oil repellency, etc. For example, it can be suitably used as a packaging material for packaging or sealing foods, medicines, cosmetics, etc. For example, a packaging bag formed using the laminate of the present invention with the porous functional layer disposed on the inside can be filled with various contents to provide a sealed packaged product. EXAMPLES

[0068] The features of the present invention will be described in more detail below with reference to examples and comparative examples, although the scope of the present invention is not limited to the examples.

[0069] Example 1 As the substrate film, a commercially available film (biaxially oriented polypropylene film (OPP)) having a thickness of 40 μm was used. A coating solution for forming a porous functional layer was prepared. Hydrophobic oxide particles with water repellency (product name: AEROSIL R812S, manufactured by Evonik Degussa, BET specific surface area: 200 m 2 The hydrophobic oxide particles were mixed with the thermoplastic resin (modified polyolefin resin, product name "Zaixen A", manufactured by Sumitomo Seika Chemicals Co., Ltd.) in ethanol and then stirred at 2000 rpm for 5 minutes using a stirrer. In this way, a coating liquid was obtained. The mass ratio of the hydrophobic oxide particles to the thermoplastic resin in the coating liquid was 50:50, and the total solid content of the hydrophobic oxide particles and the thermoplastic resin in the coating liquid was 5 mass%. The obtained coating liquid was applied to the above-mentioned film using a bar coater and dried under the conditions of 120°C x 60 seconds to form a porous functional layer. The coating amount of the porous functional layer after drying was 2.5 g / m 2 In this manner, a laminate having a porous functional layer formed on the surface of the substrate film was produced.

[0070] Example 2 A laminate was produced in the same manner as in Example 1, except that surface-modified silica fine particles obtained by the following procedure were used instead of the hydrophobic oxide fine particles. Hydrophilic silica particles (product name: AEROSIL 200, manufactured by Nippon Aerosil Co., Ltd., BET specific surface area: 200 m 2 5 g of silica particles (1.0 g / g, average primary particle diameter 12 nm) were placed in a reaction tank, and 500 g of a commercially available surface treatment agent was sprayed onto the tank while stirring under a nitrogen gas atmosphere, followed by stirring at 200°C for 30 minutes and then cooling. This resulted in a powder of surface-modified silica particles (composite oxide particles). Note that as the surface treatment agent, an aqueous dispersion (solid content concentration: 20% by mass) of a copolymer of polyfluorooctyl methacrylate, 2-N,N-diethylaminoethyl methacrylate, 2-hydroxyethyl methacrylate, and 2,2'-ethylenedioxydiethyl dimethacrylate was used.

[0071] Example 3 A laminate was produced in the same manner as in Example 1, except that an ethylene-vinyl acetate copolymer resin (product name "Sepolsion VA", manufactured by Sumitomo Seika Chemicals Co., Ltd.) (Polyolefin A) was used as the thermoplastic resin instead of the modified polyolefin resin.

[0072] Example 4 A laminate was produced in the same manner as in Example 2, except that an ethylene-vinyl acetate copolymer resin (product name "Sepolsion VA", manufactured by Sumitomo Seika Chemicals Co., Ltd.) (Polyolefin A) was used as the thermoplastic resin instead of the modified polyolefin resin.

[0073] Example 5 A commercially available film (biaxially oriented polyethylene terephthalate film (PET)) having a thickness of 25 μm was used as the substrate film. Moreover, a copolymer polyester resin (product name "Sepoljon ES", manufactured by Sumitomo Seika Chemicals Co., Ltd.) (polyester) was used instead of the modified polyolefin resin. Other than these points, a laminate was produced in the same manner as in Example 1.

[0074] Example 6 A laminate was produced in the same manner as in Example 5, except that the surface-modified silica fine particles described in Example 2 were used instead of the hydrophobic oxide fine particles.

[0075] Example 7 A commercially available film (low-density polyethylene film (LDPE)) having a thickness of 30 μm was used as the substrate film. In addition, a polyolefin resin (product name "Sepoljon G", manufactured by Sumitomo Seika Chemicals Co., Ltd.) (polyolefin B) was used instead of the modified polyolefin resin. Except for these points, a laminate was produced in the same manner as in Example 1.

[0076] Example 8 A laminate was produced in the same manner as in Example 7, except that the surface-modified silica fine particles described in Example 2 were used instead of the hydrophobic oxide fine particles.

[0077] Example 9 As the substrate film, a commercially available film (biaxially oriented polypropylene film (OPP)) having a thickness of 40 μm was used. For 100 parts by weight of a commercially available polyolefin resin coating agent (heat seal coating agent), high density polyethylene particles (HDPE, average particle size D50: 12 μm, melting point: 136 °C, density: 0.94 g / cm 3 The resulting dispersion was applied to the corona-treated surface of the film using a bar coater and dried at 80°C for 10 seconds to form a heat seal layer containing filler particles and a heat seal agent. The adhesion amount of the heat seal layer after drying was 3.0 g / m 2 It was decided. Next, a coating liquid for forming a porous functional layer was prepared. Hydrophobic oxide particles with water repellency (product name: AEROSIL R812S, manufactured by Evonik Degussa, BET specific surface area: 200 m 2 The hydrophobic oxide particles were mixed with the thermoplastic resin (modified polyolefin resin, product name "Zaixen A", manufactured by Sumitomo Seika Chemicals Co., Ltd.) in ethanol and then stirred at 2000 rpm for 5 minutes using a stirrer. In this way, a coating liquid was obtained. The mass ratio of the hydrophobic oxide particles to the thermoplastic resin in the coating liquid was 50:50, and the total solid content of the hydrophobic oxide particles and the thermoplastic resin in the coating liquid was 5 mass%. The obtained coating liquid was applied onto the heat seal layer using a bar coater, and then dried at 120°C for 60 seconds to form a porous functional layer. The coating amount of the porous functional layer after drying was 2.5 g / m 2 It was decided.

[0078] Example 10 A laminate was produced in the same manner as in Example 9, except that the surface-modified silica fine particles described in Example 2 were used instead of the hydrophobic oxide fine particles.

[0079] Comparative Example 1 A laminate was produced in the same manner as in Example 1, except that the mass ratio of the hydrophobic oxide fine particles to the modified polyolefin resin in the coating liquid was 90:10.

[0080] Comparative Example 2 A laminate was produced in the same manner as in Example 2, except that the mass ratio of the surface-modified silica fine particles to the modified polyolefin resin in the coating liquid was 90:10.

[0081] Comparative Example 3 A laminate was produced in the same manner as in Example 1, except that the mass ratio of the hydrophobic oxide fine particles to the modified polyolefin resin in the coating liquid was 40:60.

[0082] Comparative Example 4 A laminate was produced in the same manner as in Example 2, except that the mass ratio of the surface-modified silica fine particles to the modified polyolefin resin in the coating liquid was 40:60.

[0083] Comparative Example 5 The coating weight after drying is 10.0 g / m 2 A laminate was produced in the same manner as in Example 1 except for the above.

[0084] Comparative Example 6 The coating weight after drying is 10.0 g / m 2 A laminate was produced in the same manner as in Example 2 except for the above.

[0085] Comparative Example 7 The coating weight after drying is 0.3g / m 2 A laminate was produced in the same manner as in Example 1 except for the above.

[0086] Comparative Example 8 The coating weight after drying is 0.3g / m 2 A laminate was produced in the same manner as in Example 2 except for the above.

[0087] Comparative Example 9 A laminate was produced in the same manner as in Example 1, except that a polyester resin was used instead of the modified polyolefin resin.

[0088] Comparative Example 10 A laminate was produced in the same manner as in Example 2, except that a polyester resin was used instead of the modified polyolefin resin.

[0089] Comparative Example 11 A laminate was produced in the same manner as in Example 1, except that a vinyl chloride-vinyl acetate copolymer resin was used instead of the modified polyolefin resin.

[0090] Comparative Example 12 A laminate was produced in the same manner as in Example 2, except that a vinyl chloride-vinyl acetate copolymer resin was used instead of the modified polyolefin resin.

[0091] Comparative Example 13 A laminate was produced in the same manner as in Example 1, except that a copolymer amide resin was used instead of the modified polyolefin resin.

[0092] Comparative Example 14 A laminate was produced in the same manner as in Example 2, except that a copolymer amide resin was used instead of the modified polyolefin resin.

[0093] Comparative Example 15 A commercially available film (biaxially oriented polypropylene film (OPP)) having a thickness of 40 μm was used as the substrate film. Metal oxide composite particles with oil repellency (product name: AEROSIL 200, manufactured by Nippon Aerosil Co., Ltd., BET specific surface area: 200 m 2 A dispersion was prepared by adding 100% cellulose acetate (100% by weight, 10% by weight, average primary particle size: 12 nm) to ethanol. The solid content in the dispersion was 5% by mass. The dispersion was applied to the film using a bar coater and dried at 120°C for 60 seconds to form an oil-repellent layer. The coating weight of the oil-repellent layer after drying was 2.5 g / m 2 It was decided.

[0094] Test example 1 (cross-section observation and occupancy measurement) (1) Cross-section observation In the obtained laminate, a smooth cross section was created by irradiating an Ar ion beam using an ion milling device at any point in a plan view, and the formed porous functional layer including a three-dimensional network structure was confirmed by observing the treated sample with a scanning electron microscope (SEM). As a representative example, a cross-sectional image of the laminate of Example 1 is shown in Figure 2. (2) Measurement of occupancy rate In the laminate, the porous functional layer at any point in plan view was observed using a FIB-SEM (Hitachi High-Technologies Corporation "NX5000") under conditions of an electron emission current of 21900 nA, a working distance of 4.0 mm, and a magnification of 15,000 times, and observations were made at 50 nm pitches in the thickness direction, and a total of 100 observation images were prepared. The observation images were imported into a commercially available image analysis software ("Image Pro+3D module" (Media Cybernetics, USA), threshold conditions: smart analysis dark color, automatic) to create a 3D image of 5 μm x 5 μm x 7 μm in size, and then the occupancy rate of the functional particles in region A and region B was analyzed. More specifically, the 3D image was sliced ​​every 400 nm in the thickness direction from the surface of the porous functional layer, and the area ratio of the void portion to the total area of ​​the sliced ​​image was taken as the porosity. The area ratio was calculated using the image analysis software from the color tone (shade) of each sliced ​​image. The slice images were prepared by slicing to the regions where the porosity was 0% and 100%. As an example, a 3D image of the porous functional layer created by using FIB-SEM in the laminate of Example 1 is shown in Figure 3. Also, Figure 4 shows an analysis image of a portion where only the porous functional layer exists in the 3D image.

[0095] Test example 2 (water and oil repellency) Water and olive oil were used to evaluate water and oil repellency. The water- and oil-repellent surface of each sample was used as the test surface, and water or olive oil was dropped onto it to check the state of the droplet. Specifically, the test surface was placed on a 10 degree inclined surface with the test surface facing up, and 1 mL of water or olive oil was dropped onto it. If the droplet slid off, it was marked as "Good", if a small amount of droplet remained but it slid off, it was marked as "Good", and if it did not slide off, it was marked as "Poor". The results are shown in Tables 1 and 2. Pure water was used as the water. The commercially available olive oil "AJINOMOTO Olive Oil" (edible olive oil) (manufactured by Ajinomoto Co., Inc.) was used.

[0096] Test Example 3 (Wear Resistance) A Gakushin-type dye rub fastness tester (Yasuda Seiki Seisakusho Co., Ltd.) was used to evaluate durability. Each sample was cut to a size of 15 mm x 150 mm, and the stainless steel surface was brought into contact with the sample. The durability test was carried out under the following conditions: load: 4.9 N, rub distance: 100 mm, and speed: 30 strokes / min. If the water- and oil-repellency was maintained after 100 strokes, it was judged as "Good", if the water- and oil-repellency effect was lost after 50 to 100 strokes, it was judged as "Good", and if the water- and oil-repellency effect was lost after less than 50 strokes, it was judged as "Poor". The durability results are shown in Tables 1 and 2.

[0097] [Table 1]

[0098] [Table 2]

[0099] As is clear from the results in Tables 1 and 2, in Examples 1 to 10, when the porosity of the outermost surface side of the porous functional layer (area A) is 50% or more and 99% or less, and the porosity of the base film side (area B) is 1% or more and 50% or less, the porous functional layer is strongly adhered to the base film and retains voids on the outermost surface side, resulting in an ultra-water-repellent layer and an ultra-oil-repellent layer with excellent durability.

[0100] In contrast, it is found that sufficient performance cannot be obtained when the compounding ratio of the functional fine particles and the thermoplastic resin is changed in Comparative Examples 1 to 4. That is, it is found that increasing the proportion of the functional fine particles deteriorates the adhesion between the base film and the porous functional layer, and increasing the proportion of the thermoplastic resin prevents the performance of the porous functional layer from being obtained.

[0101] In Comparative Examples 5 to 8, when the amount of adhesion after drying of the mixed solution was changed, the adhesion strength between the porous functional layer and the substrate film was sufficient, but the water-repellent and oil-repellent performance was not obtained. It can be seen that if the amount of adhesion is too large, a uniform coating cannot be formed in the drying process and there are few voids. It can also be seen that if the amount of adhesion is too small, the performance of the functional agent itself is not exhibited.

[0102] In Comparative Examples 7 to 11, when a thermoplastic resin with poor adhesion to the base film (OPP) was selected, the performance as a porous functional layer was exhibited, but the adhesion to the base film was low.

Claims

1. A laminate comprising a substrate film and a porous functional layer formed on the substrate film, the porous functional layer including a three-dimensional network structure formed by bonding water-repellent and / or oil-repellent particles to each other and a thermoplastic resin, In the thickness direction of the porous functional layer, the porosity is 37 volume % or more and 48 volume % or less in a region from the bottom surface of the porous functional layer to 50% of the thickness, and the porosity is 57 volume % or more and 72 volume % or less in a region from the bottom surface of the porous functional layer to more than 50% of the thickness to the surface of the porous functional layer, The mass ratio of the fine particles to the thermoplastic resin is 50:50 to 80:

20. A laminate comprising:

2. 2. The laminate according to claim 1, wherein the voids in the three-dimensional network structure in at least a region extending from the bottom surface of the porous functional layer to 50% of the thickness are filled with a thermoplastic resin.

3. The laminate according to claim 1 or 2, wherein a portion of the porous functional layer is embedded in the substrate film.

4. The laminate according to any one of claims 1 to 3, wherein the fine particles have an average primary particle size of 5 to 50 nm.

5. The amount of the porous functional layer applied is 0.6 to 5 g / m 2 The laminate according to any one of claims 1 to 4,

6. The laminate according to any one of claims 1 to 5, wherein the thermoplastic resin comprises a polyolefin resin.

Citation Information

Patent Citations

  • Capping material

    JP2010184454A

  • Inorganic particle composite, and method for manufacturing the same

    JP2011068122A

  • Content-antisticking lid material and method for manufacturing same

    JP2011184082A

  • Water repellent laminate and lid material

    JP2013091289A

  • Manufacturing method of super water repellent material, and super water repellent material

    JP2014152389A